2014
DOI: 10.1007/s00167-014-3161-8
|View full text |Cite
|
Sign up to set email alerts
|

Bone loss in patients with posterior gleno-humeral instability: a systematic review

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 43 publications
0
36
0
Order By: Relevance
“…14 However, the size of the humeral head defect that requires bony augmentation remains unclear. 15 To better describe the relation between instability and the presence of a Hill-Sachs lesion, Yamamoto et al 16 introduced the concept of the glenoid track, which is defined as the contact zone between the glenoid and humeral head. Through this concept, the lesion is defined as either engaging or non-engaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 However, the size of the humeral head defect that requires bony augmentation remains unclear. 15 To better describe the relation between instability and the presence of a Hill-Sachs lesion, Yamamoto et al 16 introduced the concept of the glenoid track, which is defined as the contact zone between the glenoid and humeral head. Through this concept, the lesion is defined as either engaging or non-engaging.…”
Section: Discussionmentioning
confidence: 99%
“…17 To address engaging lesions, several treatment options have been reported including remplissage, [18][19][20][21] reconstruction through use of a humeral head allograft, 22 hemiarthroplasty, and arthroplasty. 15 Furthermore, bony allografts, derived from other joints, have been described as treatment options, including femoral head allografts. 22 Although the remplissage procedure is a viable treatment option, the resulting loss of external rotation has been noted as a concern, especially in throwing athletes.…”
Section: Discussionmentioning
confidence: 99%
“…39,41,47 Surgical management should be individualized to address the anatomic cause of the instability. [48][49][50][51][52][53] Even if there is no pathognomonic finding, and in 98% of MDI there is no finding at all, capsular redundancy, increased glenohumeral volume and labral abnormalities can sometimes be found. 26,39 Hyperlaxity is common in patients with MDI, often involving findings such as patulous capsular tissue, signs of generalized hyperlaxity, and recurrent subluxation.…”
Section: Recurrent Instabilitymentioning
confidence: 91%
“…10,48,65,67 Posterior instability is a common finding in the epileptic population, but there are few reports describing associated bone defects. 10,40 In a systematic review, Longo et al 40 demonstrated that in cases of posterior instability, glenoid bone loss was found in 9%, humeral head bone loss in 39%, and bipolar bone loss in 2% of shoulders. Early identification, characterization, and targeted management of these lesions are imperative as they have been recognized as independent risk factors for failure of surgical treatment.…”
Section: Pathoanatomymentioning
confidence: 99%